Stem cells supporting other stem cells - Leatherman, Judith (Frontiers in Genetics, 2013)
Adult stem cell therapies are increasingly prevalent for the treatment of damaged or diseased tissues, but most of the improvements observed to date are attributed to the ability of stem cells to produce paracrine factors that have a trophic effect on existing tissue cells, improving their functional capacity. It is now clear that this ability to produce trophic factors is a normal and necessary function for some stem cell populations. In vivo adult stem cells are thought to self-renew due to local signals from the microenvironment where they live, the niche. Several niches have now been identified which harbor multiple stem cell populations. In three of these niches—the Drosophila testis, the bulge of the mammalian hair follicle, and the mammalian bone marrow—one type of stem cell has been found to produce factors that contribute to the maintenance of a second stem cell population in the shared niche. In this review I will examine the architecture of these three niches and discuss the molecular signals involved. Together, these examples establish a new paradigm for stem cell behavior, that stem cells can promote the maintenance of other stem cells.